Fungsi Sosial Vokatif Bahasa Melayu Palembang di Kota Baturaja: Kajian Sosiolinguistik - Putri, Laily Adha Intan; Wahya, Wahya; Wagiati, Wagiati (Aksara: Jurnal Bahasa dan Sastra, 2024)
In communication, vocatives are quite often used. Vocatives are nouns whose presence is optional in a sentence and are directed at the person being spoken to (second person). The purpose of this study is to analyze how the social function of vocatives in Palembang Malay in Baturaja City. The theory of Wahya & Suparman (2023) is used in this study because it is more relevant in discussing regional language vocatives. This study is a field study with a qualitative descriptive research method. This study examines four domains, namely education, transactions, family, and intimacy so that they are located in schools, markets, residents' homes, and workspaces/classrooms. Data were collected using the listening method with basic tapping techniques and continued with recording techniques and note-taking techniques. The matching method and distributional method (agih) were used to analyze the data. The results of the data analysis are presented using informal techniques in the form of Palembang Malay data accompanied by their equivalents in Indonesian sentences in spoken language. The social functions of vocatives found in this study are (1) familiarity (full and fragmented proper names, Dek, kau, kamu); (2) politeness (Yuk/Ayuk, Buk, Bik, Cik); (3) endearment (Adek/Dek, Yuk/Ayuk, Nak), and (4) directive (full proper name, kau, kau tu). With this research, it is expected to add references on the influence of local culture in the use of vocatives and strengthen the theory of sociolinguistic studies on vocatives in regional languages in Indonesia.Keywords: vocative; Palembang Malay; social function of vocatives; sociolinguistics